PERBANDINGAN KADAR GLUKOSA DARAH PUASA ANTARA METODE GOD-PAP DAN POCT PADA KELOMPOK USIA DEWASA - Musrikatun, Laela Siti; Jimat, Resi Tondho; Ismawatie, Emma (LPPI Yayasan Almahmudi bin Dahlan, 2026)
Fasting blood glucose (FBG) is the level of glucose in the blood measured after not eating or drinking (except water) for at least 8 hours. The measurement of fasting blood glucose is an important parameter in the diagnosis and monitoring of diabetes mellitus. The GOD-PAP method is used as a standard method due to its high accuracy, while the POCT method is widely used because it is practical and provides rapid results. Differences in principles and types of specimens between the two methods may lead to variations in examination results. This study aimed to compare fasting blood glucose levels between the GOD-PAP and POCT methods in the adult age group. This research was an observational comparative study with a cross-sectional approach. The sample consisted of 35 adult respondents. Data analysis was performed using the Shapiro-Wilk test, followed by the Paired Sample t-Test. The results showed that the mean fasting blood glucose level measured by the GOD-PAP method was lower than that measured by the POCT method, with a mean difference of 46.01 mg/dL. Statistical analysis showed a p-value of 0.000 (p < 0.05), indicating a significant difference between the two methods.